Γδ T cells restrain extrathymic development of Foxp3+‐inducible regulatory T cells via IFN‐γ. Issue 8 (30th May 2014) - Visperas, Anabelle; Shen, Bo; Min, Booki
<x xml:space="preserve">Abstract</x> Inducible Treg (iTreg) cells generated from Ag‐stimulated naïve CD4+ T cells in the periphery play an important role in regulating immune responses. TGF‐β is a key cytokine that promotes this conversion process; however, how this process is regulated in vivo remains unclear. Here, we report that γδ T cells play a crucial role in controlling iTreg generation and suppressor function. Ag‐induced iTreg generation was significantly enhanced in C57BL/6 mice in the absence of γδ T cells. Inhibition of iTreg conversion was mediated by IFN‐γ produced by activated γδ T cells but not by activated CD4+ T cells. BM chimera experiments further confirmed γδ‐derived IFN‐γ‐dependent mechanism in regulating iTreg generation in vivo. Lastly, human peripheral blood γδ T cells also interfere with iTreg conversion via IFN‐γ. Our results suggest a novel function of γδ T cells in limiting the generation of iTreg cells, potentially balancing immunity and tolerance.